3D-printed biopolymer-based microneedle for enhanced photodynamic therapy in melanoma treatment - Obalola, Aishat Adejoke; Abrahamse, Heidi; Dhilip Kumar, Sathish Sundar (Frontiers in Oncology, 2025)
Melanoma is a highly aggressive cancer with poor prognosis and resistance to many treatments, especially after metastasis. Developing new preventive and adjuvant therapies is critical for improving melanoma outcomes. Photodynamic therapy (PDT) has shown potential in selectively targeting malignant cells while minimizing damage to healthy tissue. However, improving the delivery of photosensitizers (PS) to melanoma cells while reducing systemic toxicity remains a challenge. Microneedles, a transcutaneous drug delivery method, offer advantages such as better patient compliance and easier management compared to traditional methods like intramuscular or intravenous injection. Despite these benefits, manufacturing precise microneedles remains a hurdle. Recent research has focused on 3D printing techniques for creating transdermal drug delivery devices, including microneedles. This review summarizes recent advantages in 3D printed biopolymer-based drug delivery systems using microneedles, evaluates their potential, and discusses the challenges and future prospects of 3D printing in transdermal therapy.